2020
DOI: 10.1051/parasite/2020058
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of Cryptosporidium spp. and Giardia duodenalis in dairy cattle in Gansu, northwest China

Abstract: Cryptosporidium spp. and Giardia duodenalis are common gastrointestinal parasites with a broad range of hosts, including humans, livestock, and wildlife. To examine the infection status and assess the zoonotic potential of Cryptosporidium spp. and G. duodenalis in dairy cattle in Gansu, China, a total of 1414 fecal samples were collected from the rectum, with one sample collected from each individual animal. All the samples were tested using nested PCR based on the small subunit ribosomal RNA (SSU rRNA) gene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
(52 reference statements)
3
15
0
Order By: Relevance
“…The investigation source of the two infections may be difficult in absence of sub-Assemblage analysis, but in the present study, we may explain the prevalence of Assemblage A & B in fecal samples (Molina et al, 2011). Close contact with a human in agriculture and rural communities provide the opportunity for transmission from animals to humans as reported in the previous studies (Wegayehu et al, 2016).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The investigation source of the two infections may be difficult in absence of sub-Assemblage analysis, but in the present study, we may explain the prevalence of Assemblage A & B in fecal samples (Molina et al, 2011). Close contact with a human in agriculture and rural communities provide the opportunity for transmission from animals to humans as reported in the previous studies (Wegayehu et al, 2016).…”
Section: Discussionsupporting
confidence: 47%
“…In sheep, Giardia were 25%, which agreed with Sahraoui et al (2019) in Algeria who found 23/83 (28%) of sheep were infected giardiasis. But, in China higher infection rates of G. intestinalis were reported for sheep 4.64% in Heilongjiang (Zhang et al, 2012) and 5.24% in Henan (Wang et al, 2016). In contrast, by nPCR the present results were lower than in China that were 64.11%, by nPCR detection followed by sequence analysis of the small subunit ribosomal RNA (SSU rRNA) gene (Cao et al, 2020).…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies in China, the UK and the USA have shown age-related variations in the distribution of different Cryptosporidium spp. in both dairy and beef cattle, with C. parvum being responsible for most infections in pre-weaned calves under 2 months of age, whereas C. bovis and C. ryanae are found predominantly in post-weaned calves and C. andersoni is much more prevalent in yearlings and adult cattle [6,18,[22][23][24]. However, other studies have found that cattle of all ages are susceptible to different Cryptosporidium species, suggesting that this may not be an age-related pattern.…”
Section: Discussionmentioning
confidence: 99%
“…However, a comprehensive analysis of available data from cattle worldwide has consistently demonstrated the presence of four major species including C. parvum together with the host-adapted C. andersoni, C. bovis and C. ryanae, mainly related to asymptomatic infections [6,18]. A number of investigations have also reported that the global distribution of these four Cryptosporidium species is age-related, with C. parvum being predominant in suckling calves, whereas C. bovis and C. ryanae are mostly found in post-weaned calves and C. andersoni in yearlings and adult cattle [6,12,[19][20][21][22][23][24]. These results suggest that only pre-weaned calves, the major carriers of the zoonotic and pathogenic species C. parvum, pose a risk for both animal and public health.…”
Section: Introductionmentioning
confidence: 99%
“…incidence in cattle is mostly attributed to four species: C. andersoni, C. bovis, C. parvum, and C. ryanae [3]. Remarkably, an age-related scattering pattern has been noted, with C. bovis and C. ryanae being prevalent in post-weaned calves, while C. andersoni being the main infective species in adults [13,[16][17][18][19][20][21][22]. The latter three species have non or low pathogenic potential and seem to be host-adapted [23][24][25].…”
Section: Introductionmentioning
confidence: 99%